ОЦІНКА ДІЯЛЬНОСТІ ПІДПРИЄМСТВ МІСТ ТА РАЙОНІВ ЗАКАРПАТСЬКОЇ ОБЛАСТІ МЕТОДОМ АНАЛІЗУ ІЄРАРХІЙ (International Journal of Innovative Technologies in Economy, 2020)
The article assesses the results of activity of enterprises of cities and districts of Zakarpattya region with the use of the Saati method.The conducted studies on this method allowed to obtain an assessment of the activities of enterprises by integrating several indicators, by quantifying the level of industrial activity, to identify those criteria, which will allow for the adoption of the right managerial decisions to improve the efficiency of industrial policy in the region, to identify depressed areas that need investment and state regulation .The scientific novelty consists in the construction of a hierarchical model for evaluating industrial policy using fully matched matrices of pairwise comparisons obtained through the transformation of economic activity indices into dimensionless criteria of Thomas Saati's hierarchical model.